PENGARUH PENAMBAHAN STABILIZER CMC TERHADAP TINGKAT PENERIMAAN ORGANOLEPTIC VELVA NENAS - Gustiarini Rika Putri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Velva is one dessert with fruit as raw material. To get the characteristics of velva can resemble ice cream stabilizer ingredients required in making the velva. One of the usual stabilizer ingredients used in food processing is Carboxy Methyl Cellulose (CMC). The purpose of the research was to determine the precise concentration of CMC in the manufacture of velva pineapple so that the resulting product to the organoleptic characteristics those consumers liked. The research method was done with some pineapple velva treatment: A (0.1% CMC addition), B (addition of 0.2% CMC, C (0.3% CMC addition), D (0.4% CMC addition), E (addition of 0.5% CMC), F (0.6% CMC addition). Observations were made to the velva pineapples namely organoleptic flavor, color, aroma and texture of velva pineapples. The results showed that the addition of the CMC 0.6% generating the best velva with fondness value (3.96) texture, (3.68) color, (3.6) taste, and (3.32) aroma.